THE INFLUENCE OF THE TAX POLICIES, THE TAX REGULATIONS, THE TAX ADMINISTRATION AND THE TAX RATE AGAINST THE MANAGEMENT MOTIVATION OF THE COMPANIES WHO CONDUCT THE TAX PLANNING (EMPIRICAL STUDY ON TAXPAYER AGENCY AT KPP MADYA PEKANBARU) - Rio Safriadi; Amir Hasan; Andreas Andreas (Jurnal Ekonomi, 2018)
This research is conducted to examine whether the faktors of the tax policies, the tax regulations, the tax administration and the tax rate which take effect against the management motivation of the companies who conduct the tax planning. This research is conducted against the corporate tax payers who are registered in tax service office Madya Pekanbaru. To examine this reserch’s hypothesis, the author uses the multiple regression analysis by using SPSS version 21.0.This research’s result reveals that there is a positive influence of the tax policies, the tax regulations, the tax administration and the tax rate varibles against the management motivation of the companies who conducted the tax planning